Quantum Spin Hall Materials. Issue 10 (11th July 2019) - Cao, Chuanwu; Chen, Jian‐Hao
Abstract: The quantum spin Hall (QSH) effect describes the state of matter in certain 2D electron systems, in which an insulating bulk state arises together with helical states at the edge of the sample. In stark contrast to its closest kin, the integer quantum Hall state, the QSH state exists only in time‐reversal symmetric system (e.g., in non‐magnetic materials and without the application of external magnetic field). This article reviews the development of the understanding and construction of the QSH states after their first theoretical proposal, with an emphasis on the materials perspective. Certain semiconductor quantum wells and 2D materials with strong spin–orbit coupling have been found to support QSH states. Abstract : In quantum spin Hall state, the electron system is two‐dimensional with insulating bulk and time‐reversal symmetry protected helical edge states. Such edge states provide a possible solution to future low‐power consumption electronics and quantum computing. This article reviews the recent development of quantum spin Hall effect with an emphasis on the materials perspective.